Priorities for family physician and general practitioner recruitment and retention in Singapore: a prioritize study - Tudor Car, Lorainne (2022)
A shortage of primary care physicians has been reported in many countries. Primary care systems are diverse and the challenges leading to a decline in workforce are at times context-specific and require tailored solutions. Inviting frontline clinicians to share their insights can help identify optimal strategies for a particular setting. To determine priorities for family physicians' and general practitioners' recruitment and retention in Singapore, we invited primary care physicians to rank pertinent strategies using PRIORITIZE, a transparent, systematic priority-setting approach.